Forensics : the scene of the crime - Peppas, Lynn (St. Catharines, ON : Crabtree Publishing Company, 2015)
Cold case files dont stay cold for very long anymore. After the medical and police teams have secured the area, the crime scene investigators arrive on the scene. This fascinating book follows the efforts of the different CSI personnel involved in gathering and analyzing the physical evidence of a crime, performing ballistics and DNA tests, following the digital trail through mobile device forensics, and giving evidence in court.
Forensic discoveries -- Forensics at work -- Types of evidence -- Ballistics, blood, and DNA -- Arson and explosives -- The future of forensics -- Learning more.
Includes bibliographical references (page 46) and index.
Guided reading: N.
Keywords: Forensic sciences -- Juvenile literature